Impact of social media usage towards academic performance among International Islamic University Malaysia (IIUM) students - Nur Hafifah binti Jamalludin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Social media is widely used in the academic field. It helps students in their study where they can easily catch-up with the latest online information and material. Previous studies also find that social media contributes to better academic performance. As such, this study investigates the impact on social media usage towards academic performance among International Islamic University Malaysia (IIUM) students guided by the Social Information Processing Theory (SIP). This study addresses the following objectives: (1) to identify patterns of social media use among IIUM students, (2) to determine the level of social media for educational use and its motives for social media usage among IIUM students, (3) to determine the extent of educational-information sharing and level of academic performance among IIUM students, (4) to analyse the relationships between social media for educational use, motives and educational-information sharing with academic performance of IIUM students, (5) to test the mediating effect of educational-information sharing between social media for educational use and students' academic performance, and (6) to test the mediating effect of educational-information sharing between motives for social media usage and students' academic performance. This study employs a quantitative research design using the survey method with a questionnaire as an instrument for data collection. Using stratified random sampling, a total of 440 undergraduate students from the Islamic Revealed Knowledge and Human Sciences (KIRKHS) Kulliyyah participated in this study. The stratum is based on the division. The study finds that students' academic performance is significantly correlated with the use of social media for education, motives for social media usage and their educational-information sharing activities. Educational-information sharing is found to partially mediate the relationship of social media for educational use, motives for social media usage and academic performance. Therefore, this study contributes to the positive usage of social media for study purposes upon improving their academic performance. Thus, the Social Information Processing (SIP) Theory holds true.